The symbolism and survivability of royal identity (RI) for the upper section of the Taoist temple built in the 19th century in the Klang Valley, Malaysia - Yeong, Yin Mei; Abd Rahman, Khairul Aidil Azlin; Ismail, Nor Atiah; Utaberta, Nangkula (University of Malaya, 2024)
Taoist temples are considered a nation-specific religious and exceptional cultural landmark regionally. The design principle of the lower, middle, and upper sections of the physical building profoundly symbolised royal identity (RI). Scholars discovered that despite Chinese lineage positively recognising the importance of this symbolism, they were clueless about it, notably the configuration of the upper section. The objective of this paper is primarily to identify the design symbolism of the Taoist temple and assess the survivability of the RI for the upper section: 1) roof form; 2) ornamentation and 3) roof colour. Qualitative research was administered by conducting an observational study amongst the ten selected Taoist temples constructed in the 19th century in the Klang Valley. The results revealed that most of the design symbolisms inherited from the Southern region of Mainland China and RI were lessened. Interestingly, the samples synthesised the orthodox RI with indigenous local Malay vernacular architecture, the ventilated roof. The finding not only potentially intensifies the Chinese community by providing insightful knowledge, but it also eases the practical-knowledge gap amongst design practitioners and revitalises the tourism industry in the culture, arts, and heritage domains.